Program kelas unggul di MTs Negeri 2 Bandar Lampung : model evaluasi menggunakan CIPP - Rauf, Ferawati (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2022)
The excellent class program is a breakthrough in the world of education. The excellent class program aims to improve the quality of education and the quality of human resources by providing a platform for special gifted and intelligent students so that they can be given the right treatment for them. MTs Negeri 2 is a madrasa that has implemented an excellent class program. This study aims to determine the success of the implementation of the excellent class program at MTsN 2 Bandar Lampung using qualitative methods. The results showed that: a). The implementation of the excellent class program can improve student achievement, b). The number of graduate students who can be absorbed by favorite schools, c). supporting factors for the implementation of the excellent class program are the excellent class team at MTsN 2 Bandar Lampung with teachers who have good competence, the madrasa committee that supports facilitating the implementation of the excellent class program c) the inhibiting factor is that teachers are still not maximal in motivating and monitoring participants in implementing the activities in the excellent class program, the change in the learning schedule during the pandemic caused many programs not to run optimally, the accompanying teacher and the head of implementing activities in the program who did not provide periodic and periodic program implementation reports d) It is necessary to increase the ability of teachers in an effort improve professionals through the implementation of training, workshops, seminars and workshops.